Panoramic Display and Planning Simulation of Civil Engineering Project Based on Virtual Reality Technology - Zheng Wang; Chang Liu; Bin Song (Complexity)
In the traditional civil engineering industry, only abstract theoretical concepts are applied to express complex realistic contents, but this method of information transmission is sometimes very limited for engineering participants, because its expression is not comprehensive and specific and also makes the recipients have difficulty in understanding its information. The rise and development of virtual reality (VR) technology has become a good assistant to overcome this difficulty, providing an extremely effective means for displaying and simulating civil engineering project in real time. This paper introduced the methods and principles of VR platform system and structure dynamic analysis, conducted virtual scene design and three-dimensional modeling of civil engineering project, analyzed the synthetic debugging and simulation roaming of the virtual environment, proposed the engineering model of virtual construction process and planning structure calculation, discussed the realization method of virtual project management and visualization, and finally performed the simulation and its result analysis of panoramic display and planning of civil engineering project based on VR technology. The results show that the VR technology can simulate various environments and activities of civil engineering projects in advance, analyze the rationality of various schemes, and modify their different functional parameters, so it can achieve the simulation optimization of project planning, design, and construction.